As contribuições da “educação matemática: da sensibilização à construção da autonomia e consciência crítica” - Taranto, Sandra Maria Teixeira Pinheiro (2019)
This research was conducted in the school community of Engenho Novo I Campus, Colégio Pedro II, Rio de Janeiro, and it proposes to analyze the contributions of the project "Mathematics Education: Sensitization to Building Autonomy and Critical Consciousness" to the education of students. This study is inserted within the discussions regarding Mathematics Education that strive for teaching and learning processes consistent with an education dedicated to the promotion of autonomy, critical awareness and of a more just society. It highlights the importance of mathematics not only for the cognitive development, but also the political, social, formative and cultural development that this area of knowledge can help promote. Mathematics is, thus, not viewed as an end in itself, but as a means to stimulate the critical dimension of the student to act in the world. The theoretical basis is supported by studies on the notions of mathematics education, when facing the challenges of the 21st century, according to D'Ambrosio (2007), Skovsmose (2000), Bishop (2001) and Chacón (2003); the concepts of autonomy and critical awareness were developed from the contributions Freire (1980) and Habermans (1989). In addition, it was based on the theories of Hernández (1998) regarding work projects, which aim at adopting a new educational posture. This research adopts a qualitative research, descriptiveinterpretative, the research method employed was the case study, using participant observation and questionnaires as data collection instruments. The results show that the Project, because it presents characteristics such as a dialogical-problematizing environment, the promotion of reflections about social organizing and work with all dimensions of mathematics; corroborates with the student's development of autonomy and critical awareness, as the first step towards social justice.